Effectiveness of Human Capital Development Programs in Indonesia 2015-2024 - Fahmi Destry Amelia; Ida Budiarty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research evaluates the effectiveness of human capital development policies in Indonesia within the education and health sectors during the periods of 2015–2019 and 2020–2024. The analysis focuses on strategic programs implemented by the Ministry of Education and Culture and the Ministry of Health by comparing planned targets with the realization of performance indicators as stated in the Strategic Plan (Renstra) documents. The study employs a qualitative evaluative approach supported by descriptive quantitative data derived from official planning and performance reports. The findings indicate that during the 2015–2019 period, programs emphasizing the expansion of basic education and health services were relatively effective in increasing participation rates and improving equitable access. In contrast, programs aimed at enhancing the quality of human resources, particularly teacher development and institutional capacity building, showed lower levels of effectiveness due to weak performance measurement systems and inconsistent data reporting. During the 2020–2024 period, the effectiveness of most education and health programs declined significantly as a result of external shocks caused by the COVID-19 pandemic. However, health programs with strong financial protection mechanisms, such as the National Health Insurance (JKN), demonstrated greater resilience compared to other programs. The study concludes that the effectiveness of human capital development policies is strongly influenced by the clarity of performance indicators, consistency in program implementation, institutional capacity, and the ability of policies to adapt to external disruptions.